IN VITRO COMPARISON OF WHITE SPOT ONSET TIME AFTER ACIDIC BEVERAGE IMMERSION - Rakhmalita Arlini; Firlana Cahyareni; Dorisna Prijaryanti (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2026)
Background: Beverages made from apple cider vinegar, pineapple vinegar, kombucha, and lemon juice are consumed for perceived health benefits. Acid content causes enamel demineralization and white spot lesions. This condition increases the risk of tooth decay when consumed continuously with poor oral hygiene habits. The study aimed to compare the onset time of white spot lesions on enamel immersed in apple cider vinegar, pineapple vinegar, kombucha, and lemon juice under in vitro conditions. Method : The study used 40 caries-free permanent premolars divided into four groups: apple cider vinegar (ACV), pineapple vinegar (PV), kombucha (KBC), and lemon juice (LJ), with 10 samples per group. Observations were conducted every minute from the start of immersion until white spots formed on the enamel surface under standardized lighting. Result : Kruskal-Wallis test showed significant differences among groups (p=0.000). Mann-Whitney tests showed significant differences between the AC and LS groups (p=0.000), the PN and LS groups (p=0.000), and the KBC and LS groups (p=0.000). Conclusion : The study concludes that there are differences in the effects of apple cider vinegar, pineapple vinegar, kombucha, and lemon juice on the onset of white spot formation in enamel. White spot lesion formation is influenced not only by pH but also by the chemical characteristics and acid composition of each beverage, including the types of organic acids and buffering properties. Lemon juice most rapidly accelerates white spot formation compared to apple cider vinegar, pineapple vinegar, and kombucha.